GENDER Platform: Methods module kickoff workshop - CGIAR GENDER Platform (CGIAR GENDER Impact Platform, 2020)
The International Food Policy Research Institute (IFPRI), as lead of the Methods Module of the GENDER Platform, organized and hosted the workshop. The workshop was facilitated by Stephan Dohrn of Radical Inclusion and Simrin Makhija, IFPRI. The Methods Module of the GENDER Platform kicked off with a virtual workshop and consultative process designed to engage gender researchers across the CGIAR system. This workshop provided an overview of the activities planned by the module for the coming years and sought input and commitment from gender researchers across the CGIAR to shape and contribute to these activities.